2019
DOI: 10.1159/000496555
|View full text |Cite
|
Sign up to set email alerts
|

The Muddied Waters of Ibrutinib Therapy

Abstract: A 37-year-old male was admitted with an atypical presentation of central nervous system (CNS) aspergillosis while on ibrutinib therapy for a CNS relapse of mantle cell lymphoma. This case highlights the importance of a high clinical suspicion of opportunistic infections in patients receiving small-molecule kinase inhibitors. This report includes a review of reported cases of Aspergillus infections in patients receiving ibrutinib and the shared features of these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Herein, we report that 85.70% of CLL and 36.36% of NHL patients were given ibrutinib, frequently given in combination with rituximab and/or corticosteroids. Most patients receiving ibrutinib at the time of infection had received chemotherapy prior to initiating ibrutinib [ 33 , 42 , 45 , 56 , 71 , 75 ]. Only two patients were treatment naïve prior to ibrutinib therapy, and one patient began ibrutinib co-currently with chemotherapy [ 33 , 42 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we report that 85.70% of CLL and 36.36% of NHL patients were given ibrutinib, frequently given in combination with rituximab and/or corticosteroids. Most patients receiving ibrutinib at the time of infection had received chemotherapy prior to initiating ibrutinib [ 33 , 42 , 45 , 56 , 71 , 75 ]. Only two patients were treatment naïve prior to ibrutinib therapy, and one patient began ibrutinib co-currently with chemotherapy [ 33 , 42 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two further cases of IA and cryptococcal meningoencephalitis (CM) occurring early in the course of ibrutinib treatment in CLL and Waldenstrom Macroglobulinemia (WM) patients were described, in absence of classical risk factors for IFIs, such as neutropenia, lymphopenia, steroid treatment and HIV infection [33]. Beside these and other reports of sporadic cases of IA, mucormycosis and cryptococcosis [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (Tables 1, 2), the incidence of opportunistic infections was evaluated in a large cohort of patients from a single Institution, finding 3% incidence of IFIs in patients affected by CLL or other lymphoproliferative disorders, treated with ibrutinib as single agents or combined with chemotherapy or steroids, with a median follow-up of 2.7 years (range 0.03-6.4) [52]. Similarly, Ruchlemer et al reported 28 patients with relapsed/refractory CLL or non-Hodgkin lymphoma with IFIs (89% proven, 11% probable).…”
Section: Clinical Incidence Of Fungal Infections In Ibrutinib-treated Patientsmentioning
confidence: 93%
“…Overall, the commonest reported fungi were Candida, followed by P. jirovecii and Cryptococcus. In the RCTs and LTE studies, no cases of endemic mycotic infections (histoplasmosis, coccidioidomycosis and blastomycosis) were observed, but Candida albicans (n = 3) C. glabrata (n = 1) C. parapsilosis (n = 1) C. [11,77,78], pulmonary (n = 1) [79], myocardial (n = 1) [80], cryptococcosis disseminated (n = 2) [81,82], CNS (n = 4) [20,83,84], pneumonia (n = 1) [83], empyema (n = 2) [19,85], Candida pneumonia (n = 2) [86,87], mucormycosis invasive (n = 1) [86], abdominal (n = 1) [84], sinus (n = 1) [88] skin (n = 2) [89,90], PJP (n = 5) [25] Acalabrutinib (Calquence) PJP Pneumocystis jirovecii pneumonia; PCM paracoccidioidomycosis *Single centre retrospective analysis. #Meta-analysis of everolimus and temsirolimus randomised controlled trials presumably few patients were enrolled from regions where these organisms are endemic [45].…”
Section: Janus Kinase/signal Transducers and Activators Of Transcriptmentioning
confidence: 96%
“…Ibrutinib is a BTK inhibitor that results in decreased B cell survival (Table 1). Although the prominent effect is on B cells, other haemopoietic cells are affected, including T cells, natural killer cells and macrophages [11]. BTK has emerged as a key player in innate immunity.…”
Section: Bruton Tyrosine Kinase Inhibitormentioning
confidence: 99%